1993
DOI: 10.21273/hortsci.28.1.65
|View full text |Cite
|
Sign up to set email alerts
|

`Abbott Pink' Bluebonnet (Lupinus texensis Hook.)

Abstract: Additional index words. bedding plant, flower color, lupine, ornamentals breeding Bluebonnet-designated by the state legmost widespread bluebonnet (Lupinus texensis) islature as all six of the Lupinus species native is a winter annual that produces predominately to Texas-is the state flower of Texas. The violet-blue (violet-blue group 96A) (Royal Horticultural Society, 1982) flower spikes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Plants have been grown from seed in the greenhouse and transplanted successfully outdoors at the following diverse Texas locations: San Antonio (7 years at several sites), Dallas (3 years), Fredericksburg (3 years), and El Paso (2 years). Comparative trials at these locations revealed no differences in garden performance between 'Texas Maroon,' the native violet-blue bluebonnet, and the previously released 'Abbott Pink' (Parsons and Davis, 1993) and 'Barbara Bush' (Parsons et al, 1994) bluebonnets.…”
Section: Performancementioning
confidence: 80%
See 1 more Smart Citation
“…Plants have been grown from seed in the greenhouse and transplanted successfully outdoors at the following diverse Texas locations: San Antonio (7 years at several sites), Dallas (3 years), Fredericksburg (3 years), and El Paso (2 years). Comparative trials at these locations revealed no differences in garden performance between 'Texas Maroon,' the native violet-blue bluebonnet, and the previously released 'Abbott Pink' (Parsons and Davis, 1993) and 'Barbara Bush' (Parsons et al, 1994) bluebonnets.…”
Section: Performancementioning
confidence: 80%
“…Rare white and even rarer pink variants exist in native populations, and a breeding project was initiated in 1985 to develop bluebonnets with novel flower colors for use as bedding plants. 'Abbott Pink' was the first seed-propagated cultivar to be developed from this program (Parsons and Davis, 1993). The second cultivar, 'Barbara Bush' with novel lavender shade flowers, was developed more recently (Parsons et al, 1994).…”
Section: Performancementioning
confidence: 99%
“…Recently, L. texensis has been produced and marketed as bedding plants for use in the landscape . Cultivars developed to broaden the appeal of this plant include 'Abbott Pink' the first seed-propagated cultivar to be developed from this program (Parsons and Davis, 1993), 'Barbara Bush' with novel lavender shade flowers and 'Texas Maroon' with novel maroon color flowers (Mackay et al, 2000). Like many legumes, L. texensis and L. havardii seeds have hard coats that are impervious to water.…”
Section: Effect Of Scarification Seed Storagementioning
confidence: 99%
“…Color variants exist in native populations but are quite rare. 'Abbott Pink' was the first cultivar to be developed (Parsons and Davis, 1993) followed by 'Barbara Bush' lavender (Parsons et al, 1994) and 'Texas Maroon' (Mackay et al, 2000). 'Lady Bird Johnson Royal Blue' was developed by recurrently selecting for flower color and is the fourth seed-propagated cultivar to be released from this project.…”
mentioning
confidence: 99%